2013
DOI: 10.1111/jcpe.12068
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant soft tissues around implants with a modified neck surface. Part 1. Clinical and histometric outcomes: a pilot study in minipigs

Abstract: The soft tissue dimensions around all implant prototypes were similar and not affected by the implant surface modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…The soft tissue buccal dimensions were similar to the ones reported in a recently published publication in mesio‐distal sections (Liñares et al. ), and those published in similar preclinal models (Buser et al. ; Listgarten et al.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The soft tissue buccal dimensions were similar to the ones reported in a recently published publication in mesio‐distal sections (Liñares et al. ), and those published in similar preclinal models (Buser et al. ; Listgarten et al.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of roughness the TiZr‐modMA and the Ti‐modMA presented similar Sa values (Liñares et al. ). Thus, surface topography may not be a reason for this finding.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A systematic review concluded that ‘ZrO 2 may have the potential to be a successful implant material', 32 while osseointegration of Ti alloys may be called similar to Ti depending in part on the surface modification applied and resulting surface morphology and hydrophobicity. 28,33,34 …”
Section: Introductionmentioning
confidence: 99%